Evaluation of Mining Safety Management System Implementation in PT. ANTAM UBPN Sultra - Andri Estining Sejati, Suwarto, Ahmad Tarmizi Abd Karim, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
occupational safety and health in the mining sector, is an important aspect in mining business activities because it has a high risk of occupational accidents or occupational diseases. This research aims to examine the success rate of SMKP that has been implemented by companies at PT. ANTAM. This type of research is a survey with a quantitative approach. The research sample consisted of representatives from 26 work units with a total of 613 employees. Data were collected using field observations, questionnaires, and guided interviews. Data were analyzed using quantitative descriptive with percentages. The results of internal audit and questionnaire as a whole, it was found that the success of implementing SMKP was 89%. Evaluation Results of the Application of Safety Management Systems at PT. ANTAM has been implemented in line with the regulation of the Minister of Energy and Mineral Resources Decree Number 26 of 2018.